Passive restoration of native woody vegetation and soil properties following Lantana camara clearing in the Kavango–Zambezi Transfrontier Conservation Area, Zimbabwe - Buhle Francis; Charlie M. Shackleton; James Gambiza (South African Journal of Botany, 2026)

Impacts of Lantana camara invasion on livelihoods: Household perceptions from the Kavango Zambezi Transfrontier Conservation Area, Zimbabwe - Buhle Francis; Charlie M. Shackleton (Biological Invasions, 2026)
Invasive alien plants (IAP) affect rural livelihoods in both positive and negative ways, yet few studies examine how these impacts are distributed across households and contribute to vulnerability. This study assessed Impacts of Lantana camara invasion on livelihoods: Household perceptions from the Kavango Zambezi Transfrontier Conservation Area, Zimbabwe. We conducted 300 household surveys and two focus group discussions with elders across four wards invaded by L. camara and evaluated household vulnerability using a vulnerability score. Elders reported that L. camara first invaded one ward in 1942 and spread to the others within 16 years, encroaching on grazing and arable lands, reducing livestock forage and crop productivity, and affecting livelihoods. While providing ecosystem services such as material for live fences, mosquito repellent, fruits, firewood, ornaments, and poultry protection, it also imposed losses associated with eradication efforts, loss of indigenous plants, forage shortages, and the harbouring of rodents and snakes. Households reported mean annual livelihood losses of approximately US$483 and gains of about US$716. These estimates are perception-based and should be interpreted as indicative of household-level livelihood trade-offs rather than precise economic values. Despite some households reporting substantial gains, these were unevenly distributed, with most households (62%) experiencing net negative outcomes. Most households (58%) were at moderate risk from invasion, while a few (2%) faced extreme risk. These findings highlight a complex socio-economic landscape in which some households gain while others lose, suggesting that management strategies should account for both gains and losses to avoid disadvantaging vulnerable groups.

A comparative borough-level analysis of the integration and stewardship of fruit trees in public spaces in London (UK) - Arlinda Hajzeri; Charlie M. Shackleton (Urban Forestry & Urban Greening, 2025)

Urban tree cover targets: The good, the bad and the SMART - Justin Morgenroth; Kieron Doick; Richard Hauer; Dexter H. Locke; Camilo Ordóñez Barona; Lara A. Roman; Tenley M. Conway; Cynnamon Dobbs; Peter Duinker; Natalie M. Gulsrud; C.Y. Jim; Andrew K. Koeser; et al. (Urban Forestry & Urban Greening, 2025)

Understanding foraging practices in Lagos metropolis to redesign urban greenspaces in support of human-nature interactions - Opeyemi Adeyemi; Charlie M. Shackleton (Urban Forestry & Urban Greening, 2023)

A Continental-Scale Validation of Ecosystem Service Models - Simon Willcock; Danny A. P. Hooftman; Stefano Balbi; Ryan Blanchard; Terence P. Dawson; Patrick J. O’Farrell; Thomas Hickler; Malcolm D. Hudson; Mats Lindeskog; Javier Martinez-Lopez; Mark Mulligan; Belinda Reyers; et al. (Ecosystems, 2019)

A spatio-temporal, landscape perspective on Acacia dealbata invasions and broader land use and cover changes in the northern Eastern Cape, South Africa - Aidan John Gouws; Charlie M. Shackleton (Environmental Monitoring and Assessment, 2019)

Community-based natural resource use and management of Bigodi Wetland Sanctuary, Uganda, for livelihood benefits - A. Gosling; Charlie M. Shackleton; J. Gambiza (Wetlands Ecology and Management, 2017)

Woody plant species richness, composition and structure in urban sacred sites, Grahamstown, South Africa - P. De Lacy; Charlie M. Shackleton (Urban Ecosystems, 2017)

Impacts of HIV / AIDS on food consumption and wild food use in rural South Africa - Keitometsi Ncube; Charlie M. Shackleton; Brent M. Swallow; Wijaya Dassanayake (Food Security, 2016)

Knowledge, perceptions and willingness to control designated invasive tree species in urban household gardens in South Africa - Charlie M. Shackleton; R. T. Shackleton (Biological Invasions, 2016)

The benefits from and barriers to participation in civic environmental organisations in South Africa - Olivia Higgins; Charlie M. Shackleton (Biodiversity and Conservation, 2015)

Homestead greening is widespread amongst the urban poor in three medium-sized South African towns - Humphrey Kaoma; Charlie M. Shackleton (Urban Ecosystems, 2014)

Contrasting architecture of key A frican and A ustralian savanna tree taxa drives intercontinental structural divergence - Glenn R. Moncrieff; Caroline E. R. Lehmann; Jan Schnitzler; James Gambiza; Pierre Hiernaux; Casey M. Ryan; Charlie M. Shackleton; Richard J. Williams; Steven I. Higgins (Global Ecology and Biogeography, 2014)
Aim We examined differences in the architecture of A frican and A ustralian savanna trees. We sought to attribute variation in tree architecture to current environments, wood density and phylogeny, and thereby elucidate the relative importance of biogeographic idiosyncrasies versus current factors in underpinning architectural differences. Location A frica and A ustralia. Methods We compiled canopy diameters and stem diameters from 4867 trees of 97 species and heights and stem diameters from 10,786 trees of 155 species from a range of A frican and A ustralian savanna ecosystems and climates. Using B ayesian methods we first estimated continental‐scale savanna tree allometries, ignoring species differences. We then examined continental differences in species‐specific allometries accounting for trait covariation using a phylogeny of our study species. Environmental variables and wood density data were included as covariates, allowing us to assess the potential underpinning of regional differences in tree allometries by differences in current environments and traits. Results Substantial allometric differences exist between A ustralian and A frican savanna trees. A ustralian trees are on average 6 m taller at 20 cm diameter, with a 53% smaller canopy area than A frican trees. However, this extreme continental‐scale variation is driven by the architecture of only a few taxa in this study – V achellia and S enegalia versus E ucalyptus and C orymbia – rather than systematic differences between species, wood density and environment. These same genera often dominate the woody strata of S outh A frican and A ustralian savannas, respectively. Main conclusions Stark differences in the architecture of A frican and A ustralian savanna tree taxa are not a product of environmental differences and are not consistent across species. Rather, the most likely explanation is the different evolutionary histories of A frican and A ustralian savannas, which share no woody species. We consider that these architectural differences are likely to impact regional patterns of woody biomass accumulation.

Invasive alien species as drivers in socio-ecological systems: local adaptations towards use of Lantana in Southern India - Ramesh Kannan; Charlie M. Shackleton; R. Uma Shaanker (Environment, Development and Sustainability, 2014)

Reconstructing the history of introduction and spread of the invasive species, Lantana, at three spatial scales in India - Ramesh Kannan; Charlie M. Shackleton; R. Uma Shaanker (Biological Invasions, 2013)

Conservation, commercialisation and confusion: harvesting of Ischyrolepis in a coastal forest, South Africa - Charlie M. Shackleton; Fiona Parkin; Maphambe I. Chauke; Linda Downsborough; Ashleigh Olsen; Gregg Brill; Craig Weideman (Environment, Development and Sustainability, 2009)

Household attributes promote diversity of tree holdings in rural areas, South Africa - Charlie M. Shackleton; Fiona Paumgarten; Michelle L. Cocks (Agroforestry Systems, 2008)

Changes in woody community structure and composition under constrasting landuse systems in a semi‐arid savanna, South Africa - Steven I. Higgins; Charlie M. Shackleton; E. Robbie Robinson (Journal of Biogeography, 1999)
Summary We aimed to explore the farm scale effects of three landuse types, communal grazing, wildlife management and commercial cattle farming, on the woody vegetation of a semiarid savanna. Location The study farms were located within a single bioclimatic zone in semiarid savanna, South Africa. Methods The species composition and structure of woody vegetation on three farms of each of three landuse types were sampled. Results We found that communal grazing land sites were classified outside the topland‐bottomland vegetation dichotomy characteristic of this region. Comparisons of size class distributions showed the communal grazing lands had fewer small and large individuals; suggesting both lower levels of regeneration and regenerative capacity in the communal grazing lands. The species richness and biomass of woody plants was lower on communal grazing lands than on private game reserves and commercial cattle farms. The longevity of tree species explains the observed lag between changes in abundance and species loss; we consequently predict that there will be future losses of species in the communal grazing lands. By classifying species into a range of use‐categories we showed that utilization and species loss was not limited to certain plant use categories. Higher levels of wood harvesting measured in the communal grazing lands are likely to be responsible for the observed differences. Main conclusions It is concluded that communal grazing management at this study site has substantially changed the composition and structure of woody plant communities, and that these changes have reduced the current availability of natural resources and will reduce resource production in the future.

Rainfall and topo‐edaphic influences on woody community phenology in South African savannas - Charlie M Shackleton (Global Ecology and Biogeography, 1999)
Woody community phenology was studied in the central lowveld, South Africa, over a twelve month period at three sites along a rainfall gradient, with both toplands and bottomlands sampled at each site. Each month, individual plants, in replicated samples, were scored into a number of categories describing their phenological state. Position on the rainfall gradient influenced: (1) onset and magnitude of leaf emergence, (2) onset and duration of mature leaves, and (3) the proportion of leafless trees. Generally, the moist site demonstrated earlier leaf growth than the intermediate or arid sites. Emergent and mature leaves were recorded earlier, and in the case of mature leaves, retained longer. Overall, there was a lower proportion of leafless trees during the dry season at the moist site, followed by the semi‐arid site, followed by the arid site. Differences with respect to catenal position were evident for the proportion of trees in winter with mature leaves, and the proportion of trees with senescent leaves. Bottomlands had a greater proportion of trees with leaves during winter, but a lower proportion of trees recorded with senescent leaves. Both of these findings were a result of the greater proportion of evergreen species in bottomlands, as well as increased leaf retention by the deciduous species. Phenological activity of leaves was related to plant stem size. In particular, there was greater leaf retention during the dry period by small stems, relative to large stems.